The Application of Restorative Justice as an Effort to Resolve the Crime of Theft in Sukabumi Resort Area - Kusumah, Gilang Rochmat; Dwidja Priyatno; Rusman; Trini Handayani (Yayasan Studi Cendekia Indonesia (YSCI), 2025)
This research discusses the application of restorative justice in handling theft cases in the Sukabumi Police District. Restorative justice emphasises the restoration of relationships between perpetrators, victims, and society, in contrast to traditional criminal law approaches that focus more on sanctions. Using a normative juridical method, this research evaluates various obstacles in the implementation of restorative justice, such as a lack of understanding from law enforcement officials and resistance to system change. In addition, there are difficulties in achieving peace between offenders and victims, as well as the absence of legal regulations at the statutory level that fully support this concept. The research findings revealed that the implementation of restorative justice in Sukabumi jurisdiction is still structurally and procedurally constrained. Therefore, further efforts are needed to increase the understanding and awareness of the authorities and the community of the benefits of this approach to achieve fairer and humanity-focused settlements. This research is expected to contribute to the development of fairer and more effective legal policies in Indonesia.